Implementasi SIPADES dalam Administrasi Pengelolaan Aset Desa Sumber Kecamatan Kradenan Kabupaten Blora - Siti Maria Ulfa; Muhamad Nukha Murtadlo (Policy, Law and Political Research Center, 2025)
The present study is motivated by the need of village governments to manage assets in a more orderly, transparent, and accountable manner. This study aims to analyze the effectiveness of the Village Asset Management System (SIPADES) implementation in improving the administrative orderliness of village assets in Sumber Village, Kradenan Subdistrict, Blora Regency. The method used is descriptive qualitative research with data collection techniques through interviews, observations, and documentation. The research samples consist of the Village Head, Village Secretary, and SIPADES Operator of Sumber Village. The results show that SIPADES helps in digitally recording and managing village assets, thereby enhancing transparency and accountability. However, challenges such as delays in recording new assets, data inconsistencies, and manual supervision still occur. Inaccurate asset recording has the potential to cause legal issues and disputes in the future. In conclusion, SIPADES plays an important role in supporting more orderly village asset management, but improvements are needed in the data updating process and real-time supervision mechanisms. This study recommends increasing operator training and implementing real-time reporting systems to optimize SIPADES usage.